Liability Structure in Small-scale Finance : Evidence from a Natural Experiment - Carpena, Fenella; Cole, Shawn; Shapiro, Jeremy; Zia, Bilal (2012)
Microfinance, the provision of small individual and business loans, has witnessed dramatic growth, reaching over 150 million borrowers worldwide. Much of its success has been attributed to overcoming the challenges of information asymmetries in uncollateralized lending. Yet, very little is known about the optimal contract structure of such loans -- there is substantial variation across lenders, even within a particular setting. This paper exploits a plausibly exogenous change in the liability structure offered by a microfinance program in India, which shifted from individual to group liability lending. The analysis finds compelling evidence that contract structure matters: for the same borrower, required monthly loan installments are 6 percent less likely to be missed under the group liability setting, relative to individual liability. In addition, compulsory savings deposits are 19 percent less likely to be missed under group liability contracts.